The Execution Outcomes of Inadequate Confronting Education on the Education Enthusiasm of High School Students - Ristanti, Fika; Wijaya, Toni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The attendance or absence of learning enthusiasm importantly influences the achievement of student education. Learning success will be accomplished if there is a will and guide to learn. Willingness to learn is known to have a significant influence on students' learning enthusiasm which also affects their learning outcomes. The aim of this research was to analyze the execution of Inadequate Confronting Education and to clarify the effect of implementation procedures and the function of health protocols on the execution of Inadequate Confronting Education on students' education reason. This kind of research is a correlational description with a quantitative approach. The quantity of samples is 267 students. Data gotten starting a survey by a Likert scale survey that has been tried for validity and reliability. Data analysis used multiple linear regression, t test and f test. The comes about of the research specify that the functioning of Inadequate Confronting Education has been carried out well. Based on the t-test, it is identified that the significance value of the implementation procedure variable (X1) is 0.000 and the health protocol variable (X2) is 0.000, so the x variable partially influences the y variable. Based on the F test, it is known that the significance value is 0.000, so the x variable simultaneously affects the y variable. The findings of this study which are a novelty are known that there is an influence between implementation procedures and health protocols on students' learning motivation both simultaneously and partially.